A sandwich-type electrochemical immunosensor based on spherical nucleic acids-templated Ag nanoclusters for ultrasensitive detection of tumor biomarker - Chen, Huinan; Li, Yuanyuan; Song, Yuchen; Liu, Fujing; Deng, Dongmei; Zhu, Xiaoli; He, Haibo; Yan, Xiaoxia; Luo, Liqiang (Biosensors & bioelectronics, 2023)
The accurate determination of tumor biomarkers in blood is of vital significance in the diagnosis and therapy of tumor disease. In this research, an innovative sandwich-type electrochemical immunosensor is designed for the ultrasensitive determination of tumor biomarker AFP using spherical nucleic acids-templated silver nanoclusters (AgNCs) sensing platform. For this purpose, on one hand, DNA functionalized gold nanoparticles (AuNPs@DNA) is selected not only as the cross-linker to immobilize the primary antibody (anti-AFP antibody 1, Ab1) to obtain AuNPs@DNA-Ab1, but also as the template for synthesizing AgNCs on AuNPs to form AuNPs@DNA-AgNCs. On the other hand, p-sulfonated calix[4]arene (pSC4) modified Au is chosen to immobilize the secondary antibody (anti-AFP antibody 2, Ab2) through host-guest recognition between Ab2 and pSC4. When AFP is encountered, the immunoreaction signal can be significantly amplified by the electrochemical reduction of AgNCs. Under optimal circumstances, the sandwich-type electrochemical immunosensor exhibits broad limit of linearity from 0.001 to 100 ng mL−1 (R2 = 0.997) and low detection limit of 7.74 fg mL−1 (S/N = 3). The immunosensor possesses excellent repeatability and selectivity, offering a novel method for sensitive clinical diagnosis of tumor markers in human hepatocellular carcinoma. [Display omitted]